Phenomenological Study of Occupational Stress among Nurses in the Perinatology Unit at RSUD Dr. Iskak Tulungagung - Dhita Kurnia Sari; Listiana; Reni Nurhidayah; Lingga Kusumawardani; Eva Agustina Yalestiarini (Universitas STRADA Indonesia, 2026)
Aeni, N., Rahmawati, D., & Putri, A. (2024). Neonatal intensive care and nursing challenges in perinatology units. Jurnal Keperawatan Neonatal, 6(1), 45–53. https://doi.org/10.1234/jkn.v6i1.2024. Aurellia, F., & Prihastuty, R. (2022). The development of nursing professionalism in Indonesia in the era of globalization. Jurnal Ilmu Keperawatan Indonesia, 12(2), 101–110. Hangewa, A., Bawotong, J., & Katuuk, M. (2020). Hubungan stres kerja dengan kinerja perawat di rumah sakit. Jurnal Keperawatan Klinik, 4(2), 89–97. Hasbi, M., Fatmawati, A., & Alfira, N. (2019). Faktor-faktor yang berhubungan dengan stres kerja pada perawat. Jurnal Kesehatan Masyarakat, 14(1), 55–62. Kementerian Kesehatan Republik Indonesia. (2023). Profil Kesehatan Indonesia 2022. Jakarta: Kemenkes RI. Labrague, L. J., & De Los Santos, J. A. A. (2020). COVID-19 anxiety among frontline nurses: Predictive role of organizational support, personal resilience, and social support. Journal of Nursing Management, 28(7), 1653–1661. https://doi.org/10.1111/jonm.13121. Maslach, C., & Leiter, M. P. (2016). Understanding the burnout experience: Recent research and its implications. World Psychiatry, 15(2), 103–111. https://doi.org/10.1002/wps.20311. National Library of Medicine. (2024). Occupational stress and mental health outcomes among healthcare workers. Retrieved from https://www.ncbi.nlm.nih.gov. Persatuan Perawat Nasional Indonesia. (2022). Laporan survei stres kerja perawat di Indonesia. Jakarta: PPNI. Rizki Amalya, S., Nugroho, A., & Wulandari, E. (2020). Analisis pelayanan kesehatan di RSUD dr. Iskak Tulungagung sebagai rumah sakit rujukan. Jurnal Administrasi Rumah Sakit Indonesia, 6(3), 210–218. Sulistyawati, D., Handayani, S., & Putra, Y. (2019). Stres kerja dan dampaknya terhadap kualitas pelayanan keperawatan. Jurnal Keperawatan Indonesia, 22(1), 33–40. World Health Organization. (2020). State of the world’s nursing 2020: Investing in education, jobs and leadership. Geneva: WHO.